Prevalence of household food security in Kenya: a systematic review and meta-analysis - Kiboi, Willy K.; Mucheru, Patrick K.; Mututho, Leah N.; Kimiywe, Judith O.; Chege, Peter M.; Negesse, Ayenew A. (International Journal Of Community Medicine And Public Health, 2022)
Food is both a basic need and a human right. As such, food security is a critical factor in individual and social health. This study aimed at assessing the pooled prevalence of household food security in Kenya. Relevant studies were systematically searched through manual and electronic searches. We searched databases including; Scopus, Embase, Science Direct, Web of Science, PubMed, Google Scholar and Cochrane Library. The Preferred reporting items for systematic reviews and meta-analyses protocol (PRISMA-P) guideline was followed. Heterogeneity of the primary studies was examined using the Cochrane Q test statistics and I2 test. A random-effect model was used to estimate the pooled prevalence of household food security. The prevalence was determined at a 95% confidence interval with its corresponding odds at a p value of less than 0.05. A total of 15 studies were included. The pooled prevalence of household food security was 22.33% (95% CI: 16.60%-28.06%). Households in an urban setting had a lower (19.28%) food security (95% CI: 12.55%-26.01%) as compared to those in rural settings (25.27%) (95% CI: 16.60%-28.06%). Additionally, those studies conducted post the Sustainable development goals (SDGs) had a higher (24.20%) household food security prevalence (95% CI: 11.49%-36.91%) as compared to those conducted before (21.16%) (95% CI: 14.11%-28.21%). Household food security remains a major concern in the country, particularly in the urban setting. Policymakers and the Government (national and county levels) at large should upscale and accelerate efforts to improve the household food security situation.